THE ROLE OF HOTEL AND RESTAURANT TAXES AND ITS EFFECT ON BANDA ACEH’S LOCAL OWN SOURCE REVENUE - Asnita Sitompul; Sofyan Syahnur; Chairul Ichsan (Aceh International Journal of Social Science, 2014)
The purpose of this research is to describe the role and the effect of hotel and restaurant taxes on Banda Aceh’s local own source revenue. Its role will be focused on analyzing tax contribution, the efficiency and effectiveness of tax collection system. Meanwhile, its effect on local own source revenue can be identified by regression analysis for 27 years (1984-2010). The results show that the average contribution of hotel and restaurant taxes is still relatively low. Moreover, the system of tax collection in Banda Aceh has been performed efficiently and effectively. But, there is a gap between the potentiality and the realization of taxes. Furthermore, hotel and restaurant taxes are statistically significant influenced local own source revenue. Therefore, government should pay more attention to improve the tax administration system in the future, enhance the quality of tax administrator, increase tax efforts intensively than extensively, and implement rewards and punishment on the overall systems. In sum, the role and the effect of hotel and restaurant taxes can induce Banda Aceh’s local own source revenue. Keywords: Hotel and restaurant taxes, Efficiency, Effectiveness, Effect of Tax, Local Own Source Revenue